A Real‐World Observational Cohort of Patients with Hepatocellular Carcinoma: Design and Rationale for TARGET‐HCC. Issue 3 (21st December 2020) - Cabrera, Roniel; Singal, Amit G.; Colombo, Massimo; Kelley, R. Kate; Lee, Hannah; Mospan, Andrea R.; Meyer, Tim; Newell, Pippa; Parikh, Neehar D.; Sangro, Bruno; Reddy, K. Rajender; Watkins, Stephanie; et al.
Abstract : This study describes the design of the TARGET‐hepatocellular carcinoma (HCC) cohort and descriptive characteristics of the patient population at diagnosis among those who were enrolled in the cohort across academic and community clinical centers. TARGET‐HCC is a 5‐year, longitudinal, observational cohort of patients with HCC receiving care in usual clinical practice. Redacted clinical information, obtained from medical records, captures the natural history and management of the disease, including the safety and efficacy of treatment interventions used in usual clinical practice. Patients can complete patient‐reported outcome measures and provide biological specimens for future translational studies. The TARGET‐HCC study includes adults with histologic, cytologic, or radiologic diagnosis of HCC from academic and community centers in both the United States and Europe. A total of 1, 841 participants were enrolled between January 9, 2017, and July 23, 2019, at 67 sites in the United States and Europe. To date, the most common liver disease etiology in the cohort continues to be hepatitis C, although nearly half had a nonviral etiology, including alcohol‐related liver disease or nonalcoholic steatohepatitis. Most included patients were diagnosed at an early stage (Barcelona Clinic Liver Cancer Stage [BCLC] 0/A), but only approximately one third underwent curative treatment. Systemic therapy has been used in 7.3% of enrolled patients, including 45.7% of those with BCLC stage C tumors. Conclusion: Overall, the TARGET‐HCC cohort allows for the assessment of patient characteristics and investigation of new treatment paradigms and sequencing with existing agents as well as novel regimens for HCC. Abstract : TARGET‐HCC is a 5‐year, longitudinal, observational cohort of patients with hepatocellular carcinoma receiving care in usual clinical practice. The objective of this manuscript is to describe the design of the TARGET‐HCC cohort and descriptive characteristics of the patient population at diagnosis across academic and community clinical centers.